If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 49 + -3m = 4m + 14 Reorder the terms: 49 + -3m = 14 + 4m Solving 49 + -3m = 14 + 4m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-4m' to each side of the equation. 49 + -3m + -4m = 14 + 4m + -4m Combine like terms: -3m + -4m = -7m 49 + -7m = 14 + 4m + -4m Combine like terms: 4m + -4m = 0 49 + -7m = 14 + 0 49 + -7m = 14 Add '-49' to each side of the equation. 49 + -49 + -7m = 14 + -49 Combine like terms: 49 + -49 = 0 0 + -7m = 14 + -49 -7m = 14 + -49 Combine like terms: 14 + -49 = -35 -7m = -35 Divide each side by '-7'. m = 5 Simplifying m = 5
| 5+x+6x=54 | | 7t+4=2(7+5) | | -3(-3)= | | 8y+6=7y-5 | | 9v=72 | | 7x^2-2x-36=0 | | 4(3x-4)=20 | | y=-5x-17 | | -15x+18=3 | | -5r+6=8 | | 3y+12=-3y | | 10p+2+1= | | 9p-2=6 | | 2(7+5r)=3r | | 4w+5=20-w | | 4n-6-3= | | 9+6x=3x | | 16=34 | | 3-4x=27 | | 19r=57 | | 8t+7=-10 | | 5x-6=2x | | 2(r-4)=5*r+(-7) | | 5x-8=2x+12 | | 3a=15 | | 8-3z=-1 | | 6j=24 | | x-3(2x-7)=76 | | 2x-5y=-50 | | 8(z+5)-34=-2 | | 22n=418 | | 8x=22+6x |